Peranan Pemberdayaan Zakat dalam Meningkatkan Pendidikan di Desa Kuwik Kecamatan Kunjang - Ali Muchasan (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2017)
Kuwik village sub-district communities Kunjang is a very viscous environment with Islamic values, because there is a majority religion is Islam. With this condition, of course, and a duty for Muslims to carry out Shari'a Muslims who form the pillars of Islam, one of which is the payment of zakat, especially zakat Mal lately often forgotten by Muslims. The role of the empowerment of zakat in improving education in the village Kuwik District of Kunjang have a very important role where the empowerment of zakat education in the village Kuwik increasingly be enhanced and in a success, the role of the empowerment of zakat in improving education in the village Kuwik subdistrict Kunjang be successful as far as to help smooth a good education of teachers and facilities. Hope the author hopefully empowering zakat can be improved further its role, and hopefully the improvement of the zakat is increasing. May God bless, Ameen!